Establishment and characterisation of two cell lines derived from a primary adenocarcinoma of the duodenum. Issue 1 (February 1996) - Golding, M; Stamp, G W H; Oates, T; Lalani, E-N
Abstract : Aims —To establish two cell lines from a primary duodenal adenocarcinoma; to describe the morphological, growth, ploidy, and immunophenotypic characteristics of these cell lines. Methods —The cell lines, designated DAC/S and DAC/E, were characterised using both in vitro and in vivo cell culture techniques, light and electron microscopy, immunocytochemistry, and FACS analyses. Results —Both cell lines have an epithelial origin, are aneuploid and display characteristics of transformed cells. The cell lines differ from each other in morphology, doubling time and serum requirements. These cell lines are anchorage dependent and do not grow in nude mice. Conclusions —DAC/S and DAC/E cell lines are derived from neoplastic epithelium and could provide in vitro model systems for future investigations of the cell and molecular biology of duodenal neoplasia.